Psychological Impact of an Economic Crisis: A Conservation of Resources Approach - (:unkn) unknown (AMER PSYCHOLOGICAL ASSOC, 2009)
This study examined the psychological effects of an economic crisis based on Conservation of Resources (COR) stress theory. It investigated how the loss of economic resources had a psychological influence on well-being and identified which of 3 variables (the loss of economic resources, demographic characteristics, or coping strategies) had the greatest psychological influence. Psychological well-being was assessed via levels of anxiety and anger. The study provided clear support for COR theory. The loss of economic resources had a strong and mostly positive relationship to anxiety and anger. The coping strategies were the most important of several predictors. Similar studies were proposed to increase confidence in generalizing to other populations and to identify the causal links between loss of economic resources, coping, and psychological well-being.
Keywords: economic crisis; resource loss; coping; anxiety; anger